2022
DOI: 10.1002/wer.10772
|View full text |Cite
|
Sign up to set email alerts
|

Introducing bioflocculation boundaries in process control to enhance effluent quality of high‐rate contact‐stabilization systems

Abstract: High‐rate activated sludge (HRAS) systems suffer from high variability of effluent quality, clarifier performance, and carbon capture. This study proposed a novel control approach using bioflocculation boundaries for wasting control strategy to enhance effluent quality and stability while still meeting carbon capture goals. The bioflocculation boundaries were developed based on the oxygen uptake rate (OUR) ratio between contactor and stabilizer (feast/famine) in a high‐rate contact stabilization (CS) system an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The combination of HRAS systems with anaerobic membrane bioreactors (AnMBR) is another feasible technology, where the COD capture efficiency of HRAS was as high as 43% and the total COD recovery in the form of methane in AnMBR reached 30%. An automated pilot-scale HiCS system, which used real-time responses to control the oxygen uptake rate (OUR) ratio between the contact and stabilization tanks, has been investigated to improve the carbon capture efficiencies …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of HRAS systems with anaerobic membrane bioreactors (AnMBR) is another feasible technology, where the COD capture efficiency of HRAS was as high as 43% and the total COD recovery in the form of methane in AnMBR reached 30%. An automated pilot-scale HiCS system, which used real-time responses to control the oxygen uptake rate (OUR) ratio between the contact and stabilization tanks, has been investigated to improve the carbon capture efficiencies …”
Section: Introductionmentioning
confidence: 99%
“…An automated pilot-scale HiCS system, which used real-time responses to control the oxygen uptake rate (OUR) ratio between the contact and stabilization tanks, has been investigated to improve the carbon capture efficiencies. 14 Operational parameters such as dissolved oxygen (DO) and SRT play a critical role in organic carbon capture efficiency. In HRAS systems, Kinyua et al found that the concentrations of EPS proteins and polysaccharides were proportional to DO under low SRT (0.28 day) conditions.…”
Section: Introductionmentioning
confidence: 99%